A long-range cis-regulatory element for class I odorant receptor genes - Tetsuo Iwata (Nature Portfolio, 2017)
“Each olfactory sensory neuron expresses a single odorant receptor gene from either class I or class II genes. Here, the authors identify an enhancer for mouse class I genes, that is highly conserved, and regulates most class I genes expression by acting over ~ 3 megabases within the whole cluster.”